Age/BMI is a strong predictor of 30-day mortality and morbidity following total hip arthroplasty - Fakhoury, Hana M. A.; Nassereddine, Mohamad; Tamim, Hani; Memish, Ziad A.; Elahi, Muhammad Affan; Daher, Sarah; Hajeer, Ali H. (Frontiers in Surgery, 2025)
IntroductionThis retrospective cohort study investigated the “Hajeer score” (age/BMI) as a predictor of 30-day postoperative outcomes pertaining to morbidity and mortality following total hip arthroplasty.MethodsUsing the National Surgical Quality Improvement Project database from 2011 to 2021, this study analyzed perioperative factors and 30-day postoperative complications in relation to age, BMI, and the Hajeer score. The complications evaluated included venous thromboembolism, pneumonia, acute myocardial infarction, readmission rates, and 30-day mortality. Patients were categorized based on their age, BMI, and Hajeer score and adjusted odds ratios (aORS) for morbidities and mortality were calculated by multivariate logistic regression.ResultsA total of 321,973 patients who underwent total hip arthroplasty were included in this study. Risk of mortality and various other outcomes (including cardiac, respiratory, urinary, and central nervous system diseases, thromboembolism, sepsis, blood transfusion, and composite morbidity) increased with age. Conversely, a higher BMI was linked to a lower risk of mortality, cardiac and respiratory diseases, and blood transfusion. A higher Hajeer score (>3) was strongly associated with an increased risk of mortality [adjusted odds ratio [OR]: 20.06, 95% confidence interval [CI]: 2.81–143.08, p < 0.05], cardiac diseases (adjusted OR: 8.53, 95% CI: 1.19–60.96, p < 0.0001), respiratory diseases (adjusted OR: 1.40, 95% CI: 1.40–1.41, p < 0.0001), and blood transfusion (adjusted OR: 2.12, 95% CI: 1.73–2.60, p < 0.05).ConclusionThe Hajeer score could be a more effective predictor of short-term (30-day) postoperative outcomes than either age or BMI alone.